Pengaruh Jenis Pelarut dan Waktu Ekstraksi Pada Metode Microwave Assisted Extraction Terhadap Karakteristik Pewarna Ekstrak Kulit Buah Naga Kuning (Selenicereus megalanthus) - Ita Purnami, Gusti Ayu; Diah Puspawati, Gusti Ayu Kadek; Kartika Pratiwi, I Desak Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
This study aimed to determine the effect of the type of solvent and extraction time using the extraction method of Microwave Assisted Extraction (MAE) on the pigment characteristics of the yellow pitaya peel extract and to find the right type of solvent and extraction time to produce yellow pitaya peel extract with the best colorant characteristics. The research design used was a randomized block design with 2 factors. First factor was type of solvent (ethanol, ethyl acetate, and n-hexane). Second factor in extraction time of MAE (6,8, and 10 minutes). The treatment was repeated twice to get 18 experimental units. The data were analyzed statistically using the variance test and if the treatment had a significant effect to observed variables, it was continued with Duncan's Multiple Range Test. The results showed that the interaction of the type of solvent and extraction time had a very significant effect (P<0.01) on yield, total carotenoids, total suspended solids (TSS), L *, a *, b * values, total phenolic, antioxidant activity, and IC50. The best treatment was found in n-hexane and 10 minutes extraction time with characteristics yield 10.00%, total carotenoids 33.40 mg/g, total dissolved solids 19.54%, the brightness (L*) 41.25, redness (a*) 19.86, yellowness (b*) 53.87, total phenolic 3.09 mg GAE/g, antioxidant activity 65.97%, and IC50 777.773 ppm.